Maternal-Fetal Risk Increase From 41 Weeks of Gestation - İlknur İnegöl Gümüş; Zeynep Kamalak; Esra Aktepe Keskin; Nilgün Öztürk Turhan (Medical Network, 2007)
OBJECTIVES: We aimed to determine the maternal-fetal outcomes in pregnancies who delivered from 41 weeks of gestation. STUDY DESIGN: Obstetrics records of 619 singleton pregnants delivered at our institution were reviewed. 275 of patients who were at ≥ 41 weeks consisted of the study group. The control group was consisted of 344 of patients deliveried between 38 and 41 gestational weeks. The groups were compared on maternal datas, mode of delivery and perinatal outcomes. RESULTS: There were 135/275 (49 %) nulliparous in the study group and 114/344 (33,13 %) nulliparous in the control group ( p < 0,001). Oxytocin was given to 82,18 % and 43,89 % of the study and the control group respectively (p<0.001). Cesarean section for cephalopelvic disproportion was indicated in 48,11% of study group and 12,38 % of control group (p<0.001). Macrosomia (>4000 g) was 19,27% and 13,37% in the study and control group respectively (p=0.048). CONCLUSIONS: Closer monitoring should commence and induction of labor should be considered in gestational week 41.